Production of Shotgun Libraries Using Random Amplification. (July 2001) - Rohwer, F.; Seguritan, V.; Choi, D.H.; Segall, A.M.; Azam, F.
In the following report, thermal cycling coupled with random 10-mers as primers was used to construct randomly amplified shotgun libraries (RASLs). This approach allowed shotgun libraries to be constructed from nanogram quantities of input DNA. RASLs contained inserts from throughout a target genome in an unbiased fashion and did not appear to contain chimeric sequences. This protocol should be useful for shotgun sequencing the genomes of unculturable organisms and rapidly producing shotgun libraries from cosmids, fosmids, yeast artificial chromosomes (YACs), and bacterial artificial chromosomes (BACs).